Reliability of the Conditioned Pain Modulation Paradigm to Assess Endogenous Inhibitory Pain Pathways - Gwyn N Lewis; Heales Luke; David A Rice; Keith Rome; Peter J McNair (Pain Research and Management)
BACKGROUND: Conditioned pain modulation paradigms are often used to assess the diffuse noxious inhibitory control (DNIC) system. DNICs provide one of the main supraspinal pain inhibitory pathways and are impaired in several chronic pain populations. Only one previous study has examined the psychometric properties of the conditioned pain modulation technique and this study did not evaluate intersession reliability.